Sources in information seeking behavior at UiTM Johor / Nurhafizah Azizan … [et al.] - Azizan, Nurhafizah; Samsudin, Noor Faraliza; Osman, Suhaila; Baharin, Siti Hajar (Faculty of Information Management, 2015)
This study is attempted to determine the awareness and identify information sources consult by undergraduate's students in their process of seeking information during their learning process. Thus, understanding the basic information seeking behaviour will improve library collection and services and perhaps improving information literacy skill of undergraduate students in UiTM Johor. This quantitative study use questionnaire as instrumentation in collect data as randomly from 200 undergraduate students across four faculties and 150 filled in questionnaire were returned. Study shows that students visit library for the purpose of conducive place for reading/study and awareness towards library services highly rated to discussion room. They also seem highly rely on lecturer notes and textbook while article journal rank as third place for source of information. Therefore, through study finding it's hope that library can improve their planning and strategies in develop the collection and services to occupy and counter for the undergraduate's students information need.